2010
DOI: 10.1172/jci40645
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive assessment of chemokine expression profiles by flow cytometry

Abstract: The chemokines are a large family of mainly secreted molecules involved in the regulation of numerous physiological and pathophysiological processes. Despite many years of investigation, the precise cellular sources of most chemokines have remained incompletely defined as a consequence of the limited availability of suitable reagents to visualize the expression of chemokine proteins at the single-cell level. Here, we developed a simple flow cytometry-based assay using commercially available chemokine-specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
89
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 60 publications
(94 citation statements)
references
References 79 publications
4
89
1
Order By: Relevance
“…CD62L/CD127 downregulation) or accelerated CD8 ϩ T M differentiation (e.g., earlier CD62L/CD127 reexpression), our results clearly demonstrate a partial uncoupling of proliferative expansion and the associated phenotypic modulation. Lastly, at the level of induced cytokine and TNFSF production, we noted only a slight reduction of the IL-2 synthesis capacity of CD80/86-deficient CD8 ϩ T E , and a specific interrogation of chemokine production (19) revealed no differences between experimental and control CD8 ϩ T E populations (Fig. 2G).…”
Section: Cd80mentioning
confidence: 72%
See 1 more Smart Citation
“…CD62L/CD127 downregulation) or accelerated CD8 ϩ T M differentiation (e.g., earlier CD62L/CD127 reexpression), our results clearly demonstrate a partial uncoupling of proliferative expansion and the associated phenotypic modulation. Lastly, at the level of induced cytokine and TNFSF production, we noted only a slight reduction of the IL-2 synthesis capacity of CD80/86-deficient CD8 ϩ T E , and a specific interrogation of chemokine production (19) revealed no differences between experimental and control CD8 ϩ T E populations (Fig. 2G).…”
Section: Cd80mentioning
confidence: 72%
“…D b NP 396-404 , D b GP [33][34][35][36][37][38][39][40][41] , and I-A b GP [66][67][68][69][70][71][72][73][74][75][76][77] MHC-peptide complexes were provided as biotinylated monomers and/or fluorophore-conjugated tetramers by the NIH tetramer core facility and used for the flow cytometrybased identification of LCMV-specific CD8 ϩ and CD4 ϩ T cells as described previously (39); essentially the same results were obtained by using I-A b GP [66][67][68][69][70][71][72][73][74][75][76][77] and I-A b GP 61-80 tetramers generated in the laboratory (not shown). The methodologies for cell surface (antibodies and MHC tetramers) and intracellular staining, including the detection of cytokines, members of the tumor necrosis factor superfamily (TNFSFs), CTLA-4, chemokines, and bromodeoxyuridine (BrdU), were detailed elsewhere previously (19,35,39,49). For the identification of FoxP3 ϩ cells, we used the reagents and protocols supplied with a FoxP3 staining kit (ebioscience).…”
Section: Micementioning
confidence: 99%
“…21,24,25 SCYA3, the gene encoding for CCL3, is part of the activated B-cell signature 34 in DLBCL and functions as a predictor for poor survival in patients with DLBCL. 35 Lossos et al 35 proposed measurement of SCYA3, along with LMO2, BCL6, FN1, CCND, and BCL2 gene expression for risk stratification in DLBCL.…”
Section: Discussionmentioning
confidence: 99%
“…CCL3 and CCL4 are chemoattractants for monocytes and lymphocytes. 23 Previous in vitro and in vivo studies highlighted CCL3 as a key response gene up-regulated in normal and neoplastic B cells in response to BCR signaling, 21,24,25 and repressed by Bcl-6. 26 Previous studies from our group and other investigators demonstrated CCL3 and CCL4 overexpression by activated CLL cells 21,27,28 and elevated CCL3 and CCL4 plasma levels in CLL patients.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, as determined by granzyme B (GZMB) and CCL5 content (12,18), the entire pool of expanded donor CD8 + T cells bore hallmarks of specific activation, and both young and old II° CD8 + T E , regardless of their differential expansion, exhibited a comparable spectrum of inducible functionalities (Supplemental Figure 1, C and D). The improved accumulation of II° CD8…”
Section: Enhanced Ii° Reactivity Of Aged Cd8mentioning
confidence: 99%